35.9k views
0 votes
3. Which of the following is equivalent to the expression 44 x 4-67оа142Ob1410Ос410Od42ОeDon't Know

3. Which of the following is equivalent to the expression 44 x 4-67оа142Ob1410Ос410Od-example-1

1 Answer

1 vote

To solve the exercise you can use these rules of exponents


\begin{gathered} a^m\cdot a^n=a^(m+n) \\ \text{and} \\ a^(-m)=(1)/(m) \end{gathered}

So, in this case, you have

Using the first rule


4^4\cdot4^(-6)=4^(4-6)=4^(-2)

Using the second rule


4^(-2)=(1)/(4^2)

Then,


4^4\cdot4^(-6)=(1)/(4^2)

Therefore, the expression equivalent to the given expression is


(1)/(4^2)

and the correct answer is option a.

User Anmatika
by
4.8k points